2015
DOI: 10.1097/cad.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

2′-Hydroxy-4-methylsulfonylchalcone enhances TRAIL-induced apoptosis in prostate cancer cells

Abstract: Prostate cancer is the most common malignant cancer in men and the second leading cause of cancer deaths. Previously, we have shown that 2'-hydroxy-4-methylsulfonylchalcone (RG003) induced apoptosis in prostate cancer cell lines PC-3 and DU145. Although tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising anticancer agent, some cancer cells are resistant to TRAIL treatment. PC-3 and LNCaP prostatic cancer cell lines have been reported to be resistant to TRAIL-induced apoptosis. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Shin et al showed that when prostate cells were treated in combination with tanshinone and TRAIL, miR135a-3p expression was upregulated and DR5 activity was induced, thereby increasing TRAIL-induced apoptosis of prostate cancer cells (10). Ismail et al showed that the combination of the anticancer drug, RG003 and TRAIL could enhance TRAIL-induced apoptosis of prostate cancer cells (11). Others have reported that metformin and evodiamine could enhance the effect of TRAIL on the apoptosis of human bladder cancer cells through downregulation of c-FLIP and Mcl-1 expression (12,13) via the mTOR/S6K1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al showed that when prostate cells were treated in combination with tanshinone and TRAIL, miR135a-3p expression was upregulated and DR5 activity was induced, thereby increasing TRAIL-induced apoptosis of prostate cancer cells (10). Ismail et al showed that the combination of the anticancer drug, RG003 and TRAIL could enhance TRAIL-induced apoptosis of prostate cancer cells (11). Others have reported that metformin and evodiamine could enhance the effect of TRAIL on the apoptosis of human bladder cancer cells through downregulation of c-FLIP and Mcl-1 expression (12,13) via the mTOR/S6K1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Natural and synthetic flavonoids can sensitize cancer cells by increasing their susceptibility to TRAIL-induced apoptosis. Flavonoids (flavonols, isoflavones, chalcones) play an important role in prostate cancer chemoprevention for they enhance TRAIL-mediated apoptosis [ 52 , 53 , 54 , 55 , 56 , 57 ]. Recent studies have revealed that chalcones, such as butein, chalcone, isobavachalcone, licochalcone-A, and xanthohumol, in combination with TRAIL cause an increase in the percentage of cell death in prostate cancer cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of quercetin to interact with the survivin promoter and prevent the expression of this protein was also found ( Özsoy et al, 2020 ). Information on the effect of flavonoids on various components of the signaling system of TRAIL-dependent apoptosis is given in Table 5 ( Ismail et al, 2015 ; Han et al, 2016 ; Park et al, 2016 ; Li et al, 2017 ; Xu et al, 2018 ; Kim et al, 2020 ; Wu et al, 2020 ; Huang et al, 2021 ).…”
Section: Mechanisms Of Action Of Flavonoidsmentioning
confidence: 99%